PENGARUH KONTRIBUSI PRODUK SYARIAH TERHADAP PERTUMBUHAN ASET PADA PERUSAHAAN ASURANSI DI INDONESIA 2012-2018 - Muhyani Muhyani; Wazin Baihaqi (Syar'Insurance: Jurnal Asuransi Syariah, 2019)
The formulation of the problems in this study are: 1). How does the contribution of the product affect the growth of sharia insurance company assets in Indonesia? 2). How much influence does the product's contribution have on the growth of sharia insurance company assets in Indonesia? The purpose of this study are 1). To analyze the effect of product contributions on the growth of sharia insurance company assets in Indonesia.2). To measure how much influence the contribution of Islamic products to the growth of insurance company assets in Indonesia .. The method used in this study is a quantitative method that uses a classic assumption test, hypothesis testing, correlation coefficient test, and coefficient of determination test. The data used are secondary data. Based on the results of the T Test, the value of t calculated product contributions can be -0.501 smaller than t table 2.0345 thus there is no significant effect between the contribution of products to asset growth. While the value of R2 0.009 or (0.9%) which means that the contribution of the product affects the growth of assets by 0.09% while the remaining 99.1% is influenced by other factors not examined in this study.